Online medical education improves knowledge of clinical trial data and mechanism of action of therapies studied for the management of dementia‐related psychosis among neurologists and psychiatrists: Dementia care research (research projects; nonpharmacological)/Therapeutic strategies and interventions. (7th December 2020) - Finnegan, Thomas; Arnaud‐Hevi, Lisette; Hanley, Kelly
Abstract: Background: Psychosis is a consequence of dementia that occurs to varying levels depending on the type of dementia. Of note, it is estimated that up to 75% of people with dementia with Lewy bodies will experience psychosis compared with approximately 10% of people with frontotemporal dementia. Management of this condition is a challenge due to a lack of FDA‐approved therapies as well as the potentially serious adverse events associated with the medications currently employed. It is crucial that clinicians are aware of clinical outcomes and the mechanism of action of investigational approaches for the pharmacologic management of dementia‐related psychosis (DRP). An online educational activity was developed with the goal of improving knowledge among neurologists and psychiatrists regarding clinical trial outcomes for investigational therapies being studied in DRP. Method: An online educational intervention was developed in the form of a 30‐minute video lecture with synchronized slides. Educational effectiveness was assessed with a repeated pairs pre‐/post‐ assessment study design in which each individual served as his/her own control. Responses to 3 knowledge‐based and 1 confidence‐based questions were analyzed. A chi‐square test assessed changes from pre‐ to post‐assessment. Cramer's V was used to calculate the effect size of online education. Data from the assessment were collected between September 4, 2019 and November 25, 2019. Result: A comparison of responses from pre‐ to post‐assessment questions demonstrated a considerable educational effect for neurologists' (n=365; V=0.17; P<.001) and a noticeable educational effect for psychiatrists' (n=1155; V=0.15; P<.001). Participation in this educational intervention showed improvements for both groups in the following areas (P<.05): the mechanism of action of pimavanserin; the impact of pimavanserin on cognitive function in patients with Alzheimer disease; and the mechanism of action of memantine. Activity participation resulted in 36% of neurologists and 34% of psychiatrists reporting an increase in confidence in their ability to manage DRP. Conclusion: This study demonstrated the success of a targeted online, video lecture on improving neurologists' and psychiatrists' knowledge of the mechanism of and clinical trial outcomes for therapies studied for the management of DRP. Future education should continue to address the clinical developments and practical management of DRP.